Analisis Gaya Kepemimpinan Demokratis, Transformasional, dan Situasional dalam Menghadapi Era Society 5.0 - Syuryatman Desri; Renada Amelia (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aims to analyze democratic, transformational and situational leadership styles in facing the era of society 5.0. using qualitative research methods using secondary data to analyze research literature reviews from various previous scientific articles to compile or obtain results. The results of the analysis show that the leadership style is quite good to use in welcoming the era of society 5.0 which is an era where humans will be very close to technology, namely a democratic leadership style where leaders are open in solving problems. Conclusion, the transformational style is a leadership style that is able to change and encourage people optimally, a situational leadership style is a leadership style that is able to read changes in circumstances quite well and quickly. Keywords: Leadership, technology, change